Variable Neighborhoods Search for Multi-Site Production Planning - Rizki, Agung Mustika; Yuliastuti, Gusti Eka; Mahmudy, Wayan Firdaus; Tama, Ishardita Pambudi (Journal of Information Technology and Computer Science, 2018)
In the home textile industry, production planning needs to be done so that the production costs incurred by the company can be well controlled. Production planning is a problem that cannot be solved in a short time. Problems are more complex if the company has several production branches in other cities, with rules and standards that are certainly very different from one city to another. Based on this background, an algorithm is needed that can solve production planning problems for companies with many production branches in order to obtain optimal solutions. VNS is applied by the author and produces an optimal and efficient solution because the time needed is relatively short compared to the planning carried out previously by the company.